2013
DOI: 10.1111/1744-9987.12026
|View full text |Cite
|
Sign up to set email alerts
|

Increased Blood Loss From Access Cannulation Site During Hemodialysis Is Associated With Anemia and Arteriovenous Graft Use

Abstract: Blood loss from the access cannulation site during hemodialysis (HD) treatment is inevitable. Nevertheless, during HD, excessive blood loss from the cannulation site is not uncommon. The clinical characteristics associated with it and whether such blood loss could impact on patient outcomes is unknown. This pilot study aims to identify the prevalence and risk factors associated with excessive bleeding (≥ 4 mL/session) from dialysis access cannulation site during regular HD treatments. Stable end-stage renal di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
11
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 23 publications
1
11
0
Order By: Relevance
“…(13) In turn, bleeding can lead to bruising (13) and anemia. (17) Risk for shock was also considered relevant, in agreement with the findings of studies that identified this diagnosis with a prevalence of 100%. (9) Risk for falls has also been reported, (1,2) which can be caused by the hemodynamic oscillations that occur during hemodialysis.…”
Section: Discussionsupporting
confidence: 64%
“…(13) In turn, bleeding can lead to bruising (13) and anemia. (17) Risk for shock was also considered relevant, in agreement with the findings of studies that identified this diagnosis with a prevalence of 100%. (9) Risk for falls has also been reported, (1,2) which can be caused by the hemodynamic oscillations that occur during hemodialysis.…”
Section: Discussionsupporting
confidence: 64%
“…A long delay significantly impacts the patient's quality of life by extending time to discharge, increases nursing workload, consumes valuable staff time usually dedicated to monitoring patient treatments and is likely to disturb the overall dialysis schedule organization of the hemodialysis unit. In addition, excessive post-dialysis puncture site bleeding estimated by the gauze weigh method has been recently found to be significantly associated with lower hemoglobin levels in an observational study ( 2 , 3 ). Conversely, excessive compression, especially with the use of hemostatic devices such as straps, tourniquets and rigid clamps, may damage vascular access walls and has been claimed by some authors to favor late fistula thrombosis ( 4 ).…”
Section: Introductionmentioning
confidence: 99%
“…. Indeed, our previous report using only the baseline data from this study showed that patients with excessive access bleeding are more likely to be anemic. In addition, we found that all five patients died from gastrointestinal bleeding during follow‐up experienced excessive access bleeding.…”
Section: Discussionmentioning
confidence: 68%
“…There is a well‐established method to evaluate the amount of blood loss during repeated HD access cannulation. Recently, our group reported the novel associations between excessive access bleeding with dialysis vintage, central venous stenosis, anemia and arteriovenous graft (AVG) usage . However, the association between excessive blood loss from access cannulation site and long‐term clinical outcomes remains unknown.…”
mentioning
confidence: 99%